2011
DOI: 10.1097/brs.0b013e318203e2b5
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With the Thickness of the Ligamentum Flavum

Abstract: Thickening of the LF is correlated with disc degeneration, aging, BMI, LSS, spinal level, and disc herniation. The authors concluded that thickening of the LF is due to buckling of the LF into the spinal canal secondary to disc degeneration more than to LF hypertrophy. Sex and the degree of pain were not correlated with the thickness of the LF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 13 publications
2
53
0
Order By: Relevance
“…This observation agrees with another study. 11 The pathogenesis of thickening of the LF is not well understood. Some studies have asserted that age-related fibrosis or decrease in the elastin-to-collagen ratio of the LF, along with hypertrophy of the LF, is associated with lumbar spinal stenosis, while others argued that the LF bulges inside the spinal canal and compresses nerve tissues.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation agrees with another study. 11 The pathogenesis of thickening of the LF is not well understood. Some studies have asserted that age-related fibrosis or decrease in the elastin-to-collagen ratio of the LF, along with hypertrophy of the LF, is associated with lumbar spinal stenosis, while others argued that the LF bulges inside the spinal canal and compresses nerve tissues.…”
Section: Introductionmentioning
confidence: 99%
“…1,10 The "thickening" is the buckling of the LF into the spinal canal after disc collapse. 11 To evaluate this theory, the relationship between the thickness of the LF and intervertebral disc degeneration, disc height at L2-L3, L3-L4, L4-L5, and L5 -S1 were examined; it was found that the LF was generally thicker in patients with grades IV to V degeneration than in those…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a major factor in spinal canal stenosis [6]. The pathogenesis of LF thickening has been linked to reductions in the elastin-to-collagen ratio of LF or age-related fibrosis, and is associated with LSS [6].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the LF covers a considerable portion of the lateral and posterior walls of the spinal canal. Thickening of the ligamentum flavum can compress the nerve root and dural sac, diminishing the diameter of the spinal canal, and contributing to sciatica and lower back pain [6]. However, the findings from conventional MRI are not always compatible with the clinical symptoms of spinal stenosis.…”
Section: Introductionmentioning
confidence: 98%